Did you just eat that? : two scientists explore double-dipping, the five-second rule, and other food myths in the lab - Dawson, Paul L., 1954-; Sheldon, Brian W., 1950- (W.W. Norton & Company, 2019)
"A rollicking yet rigorous inquiry that follows the science of germs into the kitchen, restaurant, and everywhere else you eat and drink. Have you ever dropped a chip on the ground, picked it up after five seconds--then eaten it? Or debated which spreads fewer germs, paper towels or electric hand dryers? What about backwash? These are perennial questions when it comes to food and germs, and Did You Just Eat That? provides the answers. Food scientists Paul Dawson and Brian Sheldon take you into their labs to show how they have determined everything from how much bacteria gets transferred from sharing utensils to how many microbes live on restaurant menus. They list their materials and methods (in case you want to replicate the experiments), guide you through their results, and offer in-depth explanations of food safety and microbiology. Written with candid humor and richly illustrated, this fascinating book will reveal surprising answers to your weirdest and most commonly debated questions about food and germs--and then some" --